COVID-19 in Human, Animal, and Environment: A Review - Swelum, Ayman A.; Shafi, Manal E.; Albaqami, Najah M.; El-Saadony, Mohamed T.; Elsify, Ahmed; Abdo, Mohamed; Taha, Ayman E.; Abdel-Moneim, Abdel-Moneim E.; Al-Gabri, Naif A.; Almaiman, Amer A.; Saleh Al-wajeeh, Abdullah; Tufarelli, Vincenzo; et al. (Frontiers in Veterinary Science, 2020)
The medical authority in China especially in Wuhan city, reported on December 2019 a large number of highly fatal, rapidly spread viral pneumonia caused by unknown coronavirus. The common history of all patients was their visiting to Wuhan Whole food store, where live animals and seafood are sold. Irrespective of the efforts of the Chinese authorities; the virus spread rapidly all over the world by travelers Provoking widespread attention by the media and panic. As many previous coronavirus epidemic had been recorded such as (SARS) which called severe acute respiratory syndrome and (MERS) which called Middle East respiratory syndrome; recently newly discovered epidemic named (COVID-19) or coronavirus disease of 2019; this disease caused by SARS Coronavirus-2 (SARS-CoV-2), this virus is in antigenically related to the SARS virus (SARS-CoV), which had been detected on 2002; depending on clinical, serological and molecular findings. There is rapid competition among the researchers to discover the source of the virus, understand the mechanism of the disease development, establish treatment strategies and determine the factors affecting the incidence of infection and severity of the disease, and focus on the production of vaccine. Corona viruses are the group of single-stranded, positive-sense RNA genome viruses; its genome length varies from 26 to 32 kilo bases. Coronavirus causes mild to severe respiratory disorders. On December 2019 several cases suffered from pneumonia of unknown causes were found in Wuhan city, which located in Hubei province in China. Chinese health authorities investigated the problem and found that new virus caused such infection and by using of next-generation sequencing found 2019 novel coronavirus (2019-nCoV). It has been transferred from humans to humans and animals to humans (zoonotic). Coronaviruses cause multiple respiratory problems; vary from common cold to severe infections such as SARS. General symptoms of infection include fatigue, cough and breathing problems such as shortness of breath, as described by World Health Organization. Serious cases may result in pneumonia, renal failure and even death. We address current information about the new SARS Coronavirus-2 as well as the COVID-19 disease caused by it in this review.